Curcumin inhibits growth and triggers apoptosis in human castration-resistant prostate cancer cells via IGF-1/PI3K/Akt pathway - Chao Chen; Qiwu Wang; Jiwen Liu (Journal of International Medical Research)
Objective This study aimed to investigate the possible mechanism by which curcumin inhibits human prostate cancer (PCa) and castration-resistant prostate cancer (CRPC). Methods CRPC cells were treated with curcumin and their viability was assessed by MTT assay and apoptosis was detected by annexinV/propidium iodide double-staining and terminal deoxynucleotidyl transferase dUTP nick-end labeling assays. Expression levels of insulin-like growth factor 1 receptor (IGF-1R) were determined by reverse transcription quantitative polymerase chain reaction (RT-qPCR) and western blotting. Phosphoinositide 3-kinase (PI3K), Akt, and forkhead box protein O1 (FOXO1) expression and phosphorylation were assessed by western blotting. Results The highly expressed PCa-related molecule IGF-1R was down-regulated in CRPC cells after curcumin treatment, as determined by RT-qPCR and western blotting. In addition, curcumin inhibited the tumor-related PI3K/Akt signaling pathway in CRPC cells. Moreover curcumin down-regulated the IGF-1/PI3K/Akt signaling pathway in tumors derived from CRPC cells. Conclusions These results demonstrated that curcumin inhibits growth and triggers apoptosis of human CRPC cells via the IGF-1/PI3K/Akt pathway, thus providing potential new therapeutic strategies for PCa and CRPC.